1990
DOI: 10.1002/ar.1092260316
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mesenchymal cell and hyaluronate distribution correlate with in vivo elevation of the mouse mesencephalic neural folds

Abstract: The mesenchyme of the elevating mesencephalic neural folds of the mouse is composed primarily of mesenchymal cells embedded in an hyaluronate-rich extracellular matrix. In this study we provide evidence that hyaluronate and mesenchymal expansion may play a role in neural fold elevation and closure. Spatial and temporal patterns of mesenchymal cell and hyaluronate distribution were analyzed during neural fold elevation and closure using the computer-assisted method of smoothed spatial averaging and established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Currently, it is generally agreed that abnormalities in the neuroepithelium and non-neuroepithelial tissues can cause neural tube defects (Shoenwolf and Smith 1990). However, only correlative evidence suggesting that head mesenchyme is required for neural tube closure has been reported (Marin-Padilla 1966;Morriss 1972;Morriss and Solursh 1978a, b;Morris-Wiman and Brinkley 1990). Here, we provide direct evidence that head mesenchyme is required for cranial neural tube formation.…”
Section: The Twist-null Mouse: a Novel Model For Neural Tube Defectssupporting
confidence: 50%
“…Currently, it is generally agreed that abnormalities in the neuroepithelium and non-neuroepithelial tissues can cause neural tube defects (Shoenwolf and Smith 1990). However, only correlative evidence suggesting that head mesenchyme is required for neural tube closure has been reported (Marin-Padilla 1966;Morriss 1972;Morriss and Solursh 1978a, b;Morris-Wiman and Brinkley 1990). Here, we provide direct evidence that head mesenchyme is required for cranial neural tube formation.…”
Section: The Twist-null Mouse: a Novel Model For Neural Tube Defectssupporting
confidence: 50%
“…Immunohistochemical studies also have identified HA-specific receptors in the cornea [25]. HA has been shown to control cell migration and growth, cellular differentiation, and tissue morphogenesis [26][27][28]. These effects of HA should facilitate wound healing and topically applied Na-HA has been reported to protect the surface structure of the corneal epithelium from chemical insult [29], increase the stability of the tear film [3] and enhance the migration of corneal epithelial cells both in vivo [5] and in vitro [6].…”
Section: Discussionmentioning
confidence: 99%
“…The elevating midbrain and hindbrain neural folds are convex, owing to the expanded extracellular matrix of the cranial mesenchyme that underlies the neuroepithelium (Morriss and Solursh, 1978;Morris-Wiman and Brinkley, 1990). Apposition of the cranial neural folds is achieved in a second phase of neurulation in which the edges of the folds bend medially, converging on the dorsal midline (Morriss-Kay, 1981).…”
Section: Differences Between Cranial and Spinal Neurulation In Mammalmentioning
confidence: 99%